The Influence of Internal Control Systems and Service Quality on Accountability with Work Culture as a Moderating Variable: Study at LP3I Banda Aceh - Novi Faurini; M. Irsan Nasution (Universitas 17 Agustus 1945 Semarang, 2025)
This study aims to analyze the impact of internal control systems and service quality on accountability and work culture at LP3I Banda Aceh. Specifically, it investigates how internal control systems influence accountability and work culture, as well as the effect of service quality on both accountability and work culture. Additionally, the research explores the role of work culture as a moderating variable in the relationship between internal control systems, service quality, and accountability. The study involves two exogenous variables, namely internal control systems and service quality, and one endogenous variable, accountability. Work culture is treated as a moderating variable. The research population includes employees and lecturers at LP3I Banda Aceh, with a total of 53 respondents in the sample. The analysis was conducted using Structural Equation Modeling (SEM) with PLS 3.0 software. The findings reveal that both internal control systems and service quality partially affect accountability and work culture. More specifically, internal control systems have a positive effect on accountability, indicating that effective internal controls contribute to higher levels of accountability within the institution. Likewise, service quality also influences accountability, suggesting that improving the quality of services leads to better accountability outcomes. Furthermore, work culture is shown to have a significant impact on accountability, reinforcing the idea that a positive work culture fosters higher levels of accountability. Importantly, the study demonstrates that work culture acts as a moderating variable, enhancing the relationship between internal control systems, service quality, and accountability. This indicates that a strong work culture can amplify the positive effects of internal control systems and service quality on accountability, contributing to the overall effectiveness of the institution.